City and state in the medieval Low Countries : collected studies by Marc Boone. - Boone, Marc, 1955- (Turnhout : Brepols, 2021)
The oeuvre of Marc Boone (Ghent, 1955) has become standard reading for specialists of medieval European towns and cities, as well as for those interested in the history of state building - most notably that of the Burgundian polity. Honoring Ghent University's venerable tradition of medieval studies begun by Henri Pirenne and building upon the work of his Doktorvater Walter Prevenier, Marc Boone also investigated taxation and the history of government spending, popular protest, and the persecution of 'deviant' sexuality. Over the course of his rich career, he served as president of the European Association of Urban History and as dean of the Faculty of Arts and Philosophy of Ghent University. For more than twenty years, he taught the introductory course on historical criticism to every first-year student of the faculty, and thus had a major impact on the pensée critique of generations of young minds. Upon the occasion of his retirement in 2021, his former students have compiled this collection of some of his best historical essays, half of which have been translated from French and Dutch into English.
boek